Review of Progress Annual Plan 1969-70 Andhra Pradesh - Planning Commission (Planning Commission, 1969)
The amount originally provided in the plan budget for 1969-70, for the normal state plan schemes was Rs. 78.50 crores as against the outlay of Rs. 62.00 crores approved by Planning Commission. The Government of India had subsequently allotted additional central assistance of Rs. 1.00 crore for Nagarjunasagar Project Left Canal, Rs. 1.00 crore for Pochampad Project and Rs. 0.25 crore for stepping up the pace of investigation and survey of potential of irrigation and power projects particularly with a view for providing additional employment opportunities for the engineering and other technical personnel.
Government of Andhra Pradesh, Planning and Co-operation Department